A longitudinal model of executive function development from birth through adolescence in children born very or extremely preterm. Issue 3 (3rd April 2019) - Stålnacke, Johanna; Lundequist, Aiko; Böhm, Birgitta; Forssberg, Hans; Smedler, Ann-Charlotte
ABSTRACT: Executive function deficits are often reported as a specific weakness in preterm children. Yet, executive function development is still not fully understood. In a prospective longitudinal study, 115 preterm born children, ≤31 weeks of gestation, were recruited at birth and subject to neuropsychological assessments at ages 5.5 and 18 years. By applying Miyake and colleagues' integrative framework of executive function to our data, two core components of executive function, working memory and cognitive flexibility, were identified through confirmatory factor analysis. Developmental stability was investigated in a serial multiple mediator structural equation model. Biological, medical, and social factors as well as mental development at 10 months were entered as predictors. Both components of executive function were highly stable from 5.5 to 18 years. Gestational age, intrauterine growth, lack of perinatal medical complications, and female sex were positively related to mental development at 10 months, which together with parental education influenced both core executive functions at 5.5 years. Working memory at 5.5 years mediated outcome in working memory at 18 years. In addition to the mediation of cognitive flexibility at 5.5 years, perinatal medical complications and restricted intrauterine growth had a continued direct negative impact on cognitive flexibility at 18 years. The application of a theoretical framework added to our understanding of executive function development in preterm born children. The study supports early identification of executive deficits among children born preterm, as deficits are unlikely to diminish with maturation.